Objectivity in Philippine news stories the case of cybercrime prevention act of 2012. - Frias, Maria Sheila F.
This content analysis of the Philippine news stories was conducted to determine whether the three big national dailies: The Philippine Star, Philippine Daily Inquirer and Manila Bulletin are objective in writing their news stories on Cybercrime Prevention Act of 2012. The results showed that none of the three newspapers were able to meet the standards of objectivity based on the Component Criteria of Objectivity by Westerstahl. Manila Bulletin, however, showed the highest number in the over-all percentage among the three. It is considered more objective compare to the other two since it dominated all the elements in the criteria having the highest percentage in each element., It is recommended that the role of the writer in the news stories analyzed in this study would be taken into considering given the fact that they are the very first "gatekeepers" of the information presented in their news stories. Also, the use of other tools to measure objectivity is recommended which would either support or contradict the results in this study, thus, making room for the newspapers companies in improving their news writing in terms of objectivity.